Enhancing strength-ductility synergy in an ex situ Zr-based metallic glass composite via nanocrystal formation within high-entropy alloy particles. (15th November 2021) - Ding, Huaping; Bao, Xiaoqian; Jamili-Shirvan, Zahra; Jin, Junsong; Deng, Lei; Yao, Kefu; Gong, Pan; Wang, Xinyun
Graphical abstract: Highlights: A strategy for designing ductile metallic glass composites by forming nanocrystals in the high-entropy alloy particles during deformation was proposed. The ex situ high-entropy alloy particle toughened Zr-based metallic glass composites were prepared by spark plasma sintering. By adding CoCrFeNiAl high-entropy alloy particles, the Zr-based metallic glass composites exhibit enhanced strength-ductility synergy. The toughening mechanisms were discussed in accordance with experiments and modeling. Abstract: In this work, we prepared equiatomic AlCoCrFeNi high-entropy alloy (HEA)-particle-toughened, Zr-based metallic glass composites by spark plasma sintering. By adding HEA particles as the second phase, the strength and plasticity of the Zr-based metallic glass composites improved concomitantly. After fracture, high-density dislocations and nanocrystals were formed in the HEA particles due to local severe plastic deformation, which consumed massive strain energy to enable the resistance to crack formation. Substantial lattice distortion imparted a remarkable work-hardening capacity to the HEAs and enhanced crack-tip dislocation trapping, and thus led to an extreme refinement of the grain size. Finite-element analyses indicated that the strain hardening behavior of HEA particles reduced the magnitude of strain localization, promoted generation of multiple shear bands, and stabilized shear band propagation. We attribute the enhanced strength-ductility synergy in the current composites to high-density dislocations and nanocrystal formation in the HEA particles, and stable propagation of multiple shear bands.